Porous Carbon Interlayer Derived from Traditional Korean Paper for Li–S Batteries - Yunju Choi; Hyungil Jang; Jong-Pil Kim; Jaeyeong Lee; Euh Duck Jeong; Jong-Seong Bae; Heon-Cheol Shin (Nanomaterials, 2024)
A carbonized interlayer effectively helps to improve the electrochemical performance of lithium–sulfur (Li–S) batteries. In this study, a simple and inexpensive carbon intermediate layer was fabricated using a traditional Korean paper called “hanji”. This carbon interlayer has a fibrous porous structure, with a specific surface area of 91.82 m2 g−1 and a BJH adsorption average pore diameter of 26.63 nm. The prepared carbon interlayer was utilized as an intermediary layer in Li–S batteries to decrease the charge-transfer resistance and capture dissolved lithium polysulfides. The porous fiber-shaped carbon interlayer suppressed the migration of polysulfides produced during the electrochemical process. The carbon interlayer facilitates the adsorption of soluble lithium polysulfides, allowing for their re-utilization in subsequent cycles. Additionally, the carbon interlayer significantly reduces the polarization of the cell. This simple strategy results in a significant improvement in cycle performance. Consequently, the discharge capacity at 0.5 C after 150 cycles was confirmed to have improved by more than twofold, reaching 230 mAh g−1 for cells without the interlayer and 583 mAh g−1 for cells with the interlayer. This study demonstrates a simple method for improving the capacity of Li–S batteries by integrating a functional carbon interlayer.